2023
DOI: 10.54112/bcsrj.v2023i1.208
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Antipyretic and Analgesic Activities of Chloroform Extract of Aloe Barbadensis Miller in Albino Rats

Abstract: The pharmacological activities of the leaf gel of Aloe vera have been extensively evaluated. Gel and latex are two basic products of aloe leaves. Latex and gel contain biologically active components. Polysaccharides contained in the leaf gel attribute most of the health benefits like anti-inflammatory, pain and fever, associated with aloe vera. In the present study, chloroform extract of A. barbadensis at various concentrations was investigated for its anti-inflammatory, antipyretic and analgesic activities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Numerous studies and clinical trials provide significant scientific evidence showing that this plant’s effectiveness is due to the synergistic effect of several bioactive components present in it [ 12 , 14 , 15 , 23 ]. The findings of various studies have shown that Aloe Vera has a strong analgesic and anti-inflammatory effect, and its use is effective for treating inflammation and controlling pain [ 24 , 25 ]. By inhibiting the growth of various pathogenic organisms, including Escherichia coli, Aspergillus niger, Candida, Staphylococcus aureus, Salmonella, Streptococcus, and Aloe Vera gel increases tissue shelf-life [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies and clinical trials provide significant scientific evidence showing that this plant’s effectiveness is due to the synergistic effect of several bioactive components present in it [ 12 , 14 , 15 , 23 ]. The findings of various studies have shown that Aloe Vera has a strong analgesic and anti-inflammatory effect, and its use is effective for treating inflammation and controlling pain [ 24 , 25 ]. By inhibiting the growth of various pathogenic organisms, including Escherichia coli, Aspergillus niger, Candida, Staphylococcus aureus, Salmonella, Streptococcus, and Aloe Vera gel increases tissue shelf-life [ 26 ].…”
Section: Introductionmentioning
confidence: 99%